2021
DOI: 10.3389/fnins.2021.665762
|View full text |Cite
|
Sign up to set email alerts
|

QPLOT Neurons—Converging on a Thermoregulatory Preoptic Neuronal Population

Abstract: The preoptic area of the hypothalamus is a homeostatic control center. The heterogeneous neurons in this nucleus function to regulate the sleep/wake cycle, reproduction, thirst and hydration, as well as thermogenesis and other metabolic responses. Several recent studies have analyzed preoptic neuronal populations and demonstrated neuronal subtype-specific roles in suppression of thermogenesis. These studies showed similar thermogenesis responses to chemogenetic modulation, and similar synaptic tracing patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…The DMH contains sympathoexcitatory neurons that innervate the rMR to drive cold-defensive, febrile and stress responses (Zaretskaia et al, 2003;Madden and Morrison, 2004;Nakamura et al, 2005;Nakamura and Morrison, 2011;Kataoka et al, 2014Kataoka et al, , 2020, and we found that cell bodies of rMR-projecting DMH neurons were more often in close contact with GABAergic axons of POA EP3R neurons than glutamatergic axons. Our Our observation that EP3Rs are expressed by both VGLUT2 mRNA-expressing and GAD67 mRNA-expressing POA neuronal groups is consistent with the recent single cell/nucleus RNA sequencing data showing Ptger3 mRNA expression in "excitatory" and "inhibitory" POA cell clusters (Moffitt et al, 2018;Upton et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The DMH contains sympathoexcitatory neurons that innervate the rMR to drive cold-defensive, febrile and stress responses (Zaretskaia et al, 2003;Madden and Morrison, 2004;Nakamura et al, 2005;Nakamura and Morrison, 2011;Kataoka et al, 2014Kataoka et al, , 2020, and we found that cell bodies of rMR-projecting DMH neurons were more often in close contact with GABAergic axons of POA EP3R neurons than glutamatergic axons. Our Our observation that EP3Rs are expressed by both VGLUT2 mRNA-expressing and GAD67 mRNA-expressing POA neuronal groups is consistent with the recent single cell/nucleus RNA sequencing data showing Ptger3 mRNA expression in "excitatory" and "inhibitory" POA cell clusters (Moffitt et al, 2018;Upton et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Our observation that EP3Rs are expressed by both VGLUT2 mRNA-expressing and GAD67 mRNA-expressing POA neuronal groups is consistent with the recent single cell/nucleus RNA sequencing data showing Ptger3 mRNA expression in “excitatory” and “inhibitory” POA cell clusters (Moffitt et al, 2018; Upton et al, 2021). The abundant GABAergic terminals of POA EP3R →DMH axons might be provided exclusively by the GAD67 mRNA-expressing population.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation that EP3Rs are expressed by both VGLUT2 mRNA–expressing and GAD67 mRNA–expressing POA neuronal groups is consistent with the recent single-cell/nucleus RNA sequencing data showing Ptger3 mRNA expression in both “excitatory” and “inhibitory” POA cell clusters ( 52 , 53 ). The abundant GABAergic axons of POA EP3R → DMH neurons might be provided exclusively by the GAD67 mRNA–expressing population.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we identified a set of tdTomato‐labeled fibers overlying optic tract RGC axons, and these appear to project to the supraoptic nucleus (SON, Figure 3a). While RGCs have been shown to innervate the peri‐SON (Beier et al., 2021; Hattar et al., 2006), Opn5 is also expressed in hypothalamic QPLOT neurons that are presynaptic to the SON, and these processes may reflect dendritic or axonal innervation by central QPLOT hypothalamic neurons (Upton et al., 2021; K. X. Zhang et al., 2020).…”
Section: Resultsmentioning
confidence: 99%